PENGARUH UKURAN PERUSAHAAN, CURRENT RATIO, DEBT TO EQUITY TERHADAP NILAI PERUSAHAAN PADA SUBSEKTOR LOGAM YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2016 - Sitorus, Friska Darnawaty; Yolanda, Yosy; Fayola, Carissa; Sherin, Sherin; Robin, Robin (Aksara Public, 2018)
This study aims to determine the effect of Company Size, Current Ratio, Debt to Equity ratio, Good corporate governance on Company Values in the metal subsector listed on the Indonesia Stock Exchange in the period 2012-2016. The results of the study show that firm size, current ratio, debt to equity ratio, good corporate governance have an effect on and are significant to the value of the company. Partially, the size of the company influences the value of the company, the current ratio affects the value of the company, the debt to equity ratio does not affect the value of the company, does not affect the value of the company.